Quality of life after nasal cancer resection: surgical versus prosthetic rehabilitation - Plath, Karim; Thielen, Hannah M.; Plath, Michaela; Baumann, Ingo; Plinkert, Peter K.; Federspil, Philippe A. (Rhinology, 2018)
BACKGROUND: Nose reconstruction following resection of nasal carcinomas is controversial. The objective of this study is to investigate the effect of surgical reconstruction versus prosthetic rehabilitation on patient quality of life (QOL). - DESIGN: This was a monocentric prospective study of patients diagnosed with nasal carcinoma from 2003 to 2013. QOL was evaluated using two organ-specific questionnaires (Rhinoplasty Outcome Evaluation [ROE] and the Functional Rhinoplasty Outcome Inventory-17 [FROI-17]) and a generic questionnaire, the Short-Form 36 Health Survey (SF-36). - MATERIAL AND METHODS: Sixty-four patients were included. Patients completed the ROE, FROI-17, and SF-36 questionnaires after nasal reconstruction. Questionnaires were completed by 62.8% of the 51 alive patients. - RESULTS: Recurrence-free survival (RFS) was 89.9%, disease-specific survival was 94.5%, and overall survival was 75.5% after five years according to the Kaplan-Meier method. Considering initial tumor stage, early stage patients had a significantly higher self-confidence score in FROI-17 subgroup analysis. In contrast, advanced stage patients showed a significantly higher score for social functioning in SF-36. Prosthetically fitted patients scored highly on the ROE questionnaire showing a high degree of aesthetic satisfaction. Surgically reconstructed patients showed a high degree of self-confidence on the FROI-17 questionnaire. However, the organ-specific ROE and FROI-17 scores were not significantly different between patients who received surgical reconstruction and prosthetic rehabilitation after oncological resection. When comparing the rehabilitation method as a function of tumor stage, there was significantly better score for physical functioning in early stage surgically reconstructed patients in the SF-36, but no significant differences in organ-specific QOL. - CONCLUSION: Surgical reconstruction and prosthetic rehabilitation after nasal cancer resection have the same effect on organ- and non-organ-specific QOL.
Gesehen am 11.03.2020